MINERAL RESOURCES OF UZBEKISTAN AND THEIR GLOBAL IMPORTANCE - Gaybullayeva , Zilola; Esonova, Feruza (Effective scientific journals, 2025)
Uzbekistan is a country rich in mineral Resources, which are important not only in the national economy, but also in the global mineral market. The country has gold, uranium, copper, coal, natural gas and other valuable mineral reserves. Gold and uranium in particular are of great importance in international trade, energy production and industry. Copper and coal, on the other hand, contribute to the development of the manufacturing industry and energy. Natural gas reserves are important not only for domestic consumption, but also for regional energy supply. Uzbekistan's strategic location in Central Asia makes it important in the supply of minerals for neighboring countries and international markets. Effective exploration, sustainable use, and management of these resources using modern technology are necessary to increase economic benefits and protect the environment. In particular, global demand for strategic metals such as uranium and copper further increases Uzbekistan's importance in the international economic and industrial system.